Entrepreneurial Intention And The Moderating Role Of Gender Evidence From Ipmi International Business School In Jakarta - Yoel Christopher Chen; Firdaus Basbeth (ADI Publisher, 2020)
Despite having the highest contribution to Indonesia GDP, the ratio of an entrepreneur to total population is only 1,7% compared to our neighbor countries Women entrepreneurs make up the majority of the founders of medium-small and enterprises, and there is a clear gap between the younger (under 35) and older generations (over 35). The study aims to investigate the intention to become an entrepreneur in the young generation in higher education and to analyze the re of gender in the relationship between entrepreneurial intention and personal attitude, subjective norms, and perceived behavioral control. This study develops a framework cross-sectional time frame in IPMI International Business School. The result demonstrates that the mean value of entrepreneurial intention was high, and there is a positive and significant effect between perceived behavioral control, personal attitude, and entrepreneurial intention. Surprisingly the subjective norms did not have a positive significant impact on entrepreneurial intention. The result indicates that students’ intention is high and gender moderated the relationships between entrepreneurial intention and persona attitude, and subjective norms, however, there is no significant effect between subjective norms and entrepreneurial intention This study fills a gap in the entrepreneurship body of knowledge by providing evidence gender moderates the relationship between personal attitude and entrepreneurial intention and between perceived behavioral control and entrepreneurial intention. This study is an empirical study that uses a SmartPLS3 with data taken from the survey of 74 students in IPMI Business School in Jakarta. The study suggests that students in universities have high intention to become an entrepreneur, and the school can gain the highest entrepreneurial intention by introducing the innovative method in teaching entrepreneurship, especially to women.